PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL DRILLINGUNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN SISTEM PERIODIK UNSUR DI KELAS X SMA NEGERI 1 INUMAN - Yunita '; Maria Erna Erna; Abdullah ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This research aims to increase student achievementon the subject Sistem periodic unsure inclass XSMAN 1 Inuman.  This research is a kind of experiment research with pretest-posttest design. The research was conducted in SMAN 1 Inuman.The samples of this research were the students of class X MIA 2 as the experimental class and  students of class X MIA 1 as  the control class.Experimental class is a class that is cooperative learning model Snowball Drilling, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic> ttable is 2,7761 > 1,66, means that the application of cooperative learning model Snowball Drilling can improve student achievement on the subject of system periodic unsurein class X SMAN 1 Inumanincrease learning achievement category in the experimental class is based on the normalized gain scores (N-Gain) relatively high at 0,7806. Keywords :Cooperative Learning ,Snowball Drilling, Learning Achievement and